1982
DOI: 10.1111/j.1348-0421.1982.tb00186.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Lyt‐1 Positive Immune T Cells in Recovery from Herpes Simplex Virus Infection in Mice

Abstract: It has been shown that T cell-mediated immunity plays a major role (4,5,(7)(8)(9)(10)12) in control of and recovery from herpes simplex virus (HSV) infection. Nevertheless, the mechanism of immune T cell-mediated protection in vivo is complex and poorly understood.Recent studies have revealed that peripheral T cells express different Lytalloantigens on their surfaces and are divisible into three subpopulations with phenotypes Lyt-1.2.3, Lyt-l, and Lyt-2.3 (2). Lyt-1.2.3 cells are presumed to be precursors for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 16 publications
2
15
0
Order By: Relevance
“…In previous studies from this and other laboratories, it has been shown that Lyt 1 + T cells may play a central role in protection against HSV infeetion (17,19,22). Immune cells of this phenotype confer protective activity by elieitation of the delayed-type hypersensitivity reaction (17,19) or accelerated antibody production (22).…”
Section: Discussionmentioning
confidence: 93%
“…In previous studies from this and other laboratories, it has been shown that Lyt 1 + T cells may play a central role in protection against HSV infeetion (17,19,22). Immune cells of this phenotype confer protective activity by elieitation of the delayed-type hypersensitivity reaction (17,19) or accelerated antibody production (22).…”
Section: Discussionmentioning
confidence: 93%
“…Both protection against and recovery from HSV infections were shown to depend on the presence of I-regionrestricted helper T cells (32,33). The mechanisms underlying these results may involve the production of y-interferon (34) and the differentiation of HSV-specific cytotoxic T cells (35), both of which are mediated by T helper cells.…”
Section: Resultsmentioning
confidence: 99%
“…Adoptive transfer of T lymphocytes specific for HSV-1 antigens can confer protection from lethal HSV-1 infections in immunocompetent and immunosuppressed mice (26)(27)(28)(29)(30). In this report we have demonstrated further that the immune response to HSV-1 is also critical for control of viral spread in the brain.…”
Section: Discussionmentioning
confidence: 99%